1965
DOI: 10.2134/agronj1965.00021962005700010010x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Rate of Stocking and Per Animal and Per Acre Performance on Pasture1

Abstract: Synopsis Quantitative theory indicates that gain per animal is constant as stocking rate is increased to a “critical” point. Beyond this point gain per head is inversely related to stocking rate. Gain per acre increases linearly as stocking rate is increased to the “critical” point, then decreases linearly with further increases in stocking rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1
4

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 2 publications
4
23
1
4
Order By: Relevance
“…As indicated earlier, there is broad recognition and agreement that increasing grazing intensity, typically measured as SR, results in a decrease in individual animal performance. The specifi c nature of this decrease has been the subject of considerable discussion (Hart, 1993) and has been described as linear (e.g., Hart, 1978), curvilinear with a concave response surface (e.g., Mott, 1960), or curvilinear with a convex response surface (e.g., Petersen et al, 1965). Even if the linear model is an oversimplifi cation of the true biology of the association, it appears to adequately describe the response across all but the lowest SR in the majority of studies reported.…”
Section: Background and Basis For Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated earlier, there is broad recognition and agreement that increasing grazing intensity, typically measured as SR, results in a decrease in individual animal performance. The specifi c nature of this decrease has been the subject of considerable discussion (Hart, 1993) and has been described as linear (e.g., Hart, 1978), curvilinear with a concave response surface (e.g., Mott, 1960), or curvilinear with a convex response surface (e.g., Petersen et al, 1965). Even if the linear model is an oversimplifi cation of the true biology of the association, it appears to adequately describe the response across all but the lowest SR in the majority of studies reported.…”
Section: Background and Basis For Assumptionsmentioning
confidence: 99%
“…T he nature of the relationships of forage NVAL and quantity with individual animal performance on pasture has been evaluated and discussed for many years (Mott, 1960;Riewe, 1961;Petersen et al, 1965;Duble et al, 1971;Hart, 1978Hart, , 1993Guerrero et al, 1984;Wu and Rykiel, 1986). For example, it is known that increasing forage mass, starting from low levels of mass, is associated with greater bite weight and intake that lead to greater animal performance (Sollenberger and Burns, 2001).…”
mentioning
confidence: 99%
“…As stocking rate increases, the output per animal declines but production per hectare increases (MCMEEKAN 1956, MOTT 1960, BRYANT et al 1965, PETERSEN et al 1965. Maxinium production per hectare is obtained when loss in production per animal by increasing the stocking rate is offset by the increased number of animals carried.…”
Section: Grazing Managementmentioning
confidence: 99%
“…O produto do número de animais.dia/ha e ganho médio diário permitiu estimar o ganho de peso vivo por hectare (GPV/ha) (PETERSEN et al, 1965). O número de animais.dia foi obtido pelo número de animais mantidos em cada unidade experimental, em cada dia, multiplicado pelo número de dias que permaneceram na unidade experimental.…”
Section: Introductionunclassified